Efficient Removal 17-Estradiol by Graphene-Like Magnetic Sawdust Biochar: Preparation Condition and Adsorption Mechanism - Yahui Zhou (International Journal of Environmental Research and Public Health, 2020)
The occurrence of environmental endocrine disrupting chemicals (EDCs) in aquatic environments has caused extensive concern. Graphene-like magnetic sawdust biochar was synthesized using potassium ferrate (K2FeO4) to make activated sawdust biochar and applied for the removal of 17-estradiol (E2). The characterization showed that the surface morphology of five graphene-like magnetic sawdust biochars prepared with different preparation conditions were quite different. The specific surface area and pore structure increased with the increment of K2FeO4 addition. The results have shown that graphene-like magnetic sawdust biochar (1:1/900 °C) had the best removal on E2. The experimental results indicated that pseudo-first-order kinetic model and the Langmuir model could describe the adsorption process well, in which the equilibrium adsorption capacity (qe,1) of 1:1/900 °C were 59.18 mg·g−1 obtained from pseudo-first-order kinetic model and the maximum adsorption capacity (qmax) of 1:1/900 °C were 133.45 mg·g−1 obtained from Langmuir model at 298K. At the same time, lower temperatures, the presence of humic acid (HA), and the presence of NaCl could be regulated to change the adsorption reaction in order to remove E2. Adsorption capacity was decreased with the increase of solution pH because pH value not only changed the surface charge of graphene-like magnetic sawdust biochar, but also affected the E2 in the water. The possible adsorption mechanism for E2 adsorption on graphene-like magnetic sawdust biochar was multifaceted, involving chemical adsorption and physical absorption, such as H-bonding, π-π interactions, micropore filling effects, and electrostatic interaction. To sum up, graphene-like magnetic sawdust biochar was found to be a promising absorbent for E2 removal from water.